Study of prescribing pattern of antimicrobial agents in indoor patients of a tertiary care hospital - Deshmukh, Vinod S.; Khadke, Vyankatesh V.; Patil, Arun W.; Lohar, Pravin S. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: To evaluate prescribing pattern of antimicrobial agents in indoor patients of medicine and surgery department of SBH Government Medical College, Dhule. Methods: This was a retrospective cross sectional study carried over a period of 3 months. The patients who were admitted and received antimicrobial therapy in department of Medicine and Surgery were randomly selected and included in the study. The case record sheet and drug chart were obtained from Medical Record Section of the Hospital. The data was collected using case record form specially prepared for the study. The cases were categorised according to slightly Modified Kunin’s Criteria. Results: Total numbers of patients receiving antimicrobial therapy were 130 in medicine department and 93 in surgery department. Most commonly prescribed antimicrobial agent was cefotaxime (21.7%) in medicine and metronidazole in surgery (30.6%) department. The average number of antimicrobials per patient was found to be 1.7 and 3.02 in medicine and surgery department respectively. The switch on therapy from parenteral to oral route was employed in 16.15% patients in medicine department and 11.82% patients in surgery department. As per Kunin’s modified criteria, 66.2% and 58.06% patients received antimicrobial therapy appropriately in Medicine and surgery department respectively. Conclusion: This study highlights the problem of over-prescription of antibiotics and a trend towards polypharmacy. The interventions to rectify the problem of inappropriate use of antimicrobial agents are needed to make therapy more rational and cost effective.